Kandungan protein tempe kedelai yang berbeda bahan pengemas primer dan parameter penyimpanan - Pujiastuti, Nurkholifah; Santoso, Broto (Journal of Pharmaceutical and Sciences, 2025)
Soybean tempeh products are in great demand by most Indonesian people. The most of producers use plastic as packaging material, but some of them use natural materials such as banana leaves and teak. Soybean tempeh packaged with leaves is more popular with the public than plastic because it has a distinctive aroma and a savory taste. This study aims to determine the differences in protein content in soybean tempeh with different primary packaging materials with raw soybeans as a comparison. The three tempeh packages were produced using raw soybeans and under the same conditions. The protein content of the samples was determined by the Lowry reaction at a wavelength of 748.5 nm. This method has been determined for its validity through repeatability, linearity, and accuracy tests. Together with raw soybeans, samples that had been stored in the freezer were measured for their protein content at two different times. The Lowry method used is valid because all parameters have met the acceptance requirements where r2 linearity = 0.9954-0.9972 (> 0.9950); %RSD repeatability = 0.291-0.768 (<2%); and %recovery accuracy = 98.769-101.118% (80-120%). The average results of the protein content of raw soybeans, plastic-packaged soybean tempeh, banana leaves, and teak leaves on the 11th day were 5.531-7.967% while on the 35th day it was 5.881-7.972%. The results of the One-Way ANOVA statistical test with sig = 0.0001 (p <0.05) so it can be said that there is a significant difference between soybean tempeh with different primary packaging materials.